Harnessing delta-like ligand 3: bridging biomarker discovery to next-generation immunotherapies in refractory small cell lung cancer - Ji, Kangkang; Guo, Lin; Zuo, Dianbao; Feng, Mingqian; Chen, Xin; Zhao, Zhenggang; Tang, Jing; Chen, Guoping (Frontiers in Immunology, 2025)
Small cell lung cancer (SCLC), accounting for 10–20% of lung cancers, remains one of the most aggressive neuroendocrine malignancies, with fewer than 7% of patients surviving beyond five years. While the addition of immune checkpoint inhibitors (ICIs) to platinum-based chemotherapy has modestly improved outcomes, long-term benefits are limited to a subset of patients, highlighting the critical need for reliable biomarkers and innovative therapies. Delta-like ligand 3 (DLL3), a Notch signaling regulator overexpressed in 70–80% of SCLC tumors, has emerged as a simultaneous biomarker and therapeutic target. This review aims to synthesize recent advances in DLL3-targeted strategies, bridging biomarker-driven diagnostics to next-generation immunotherapies, while addressing clinical challenges and future directions. The 2024 FDA approval of tarlatamab—a bispecific T-cell engager (BiTE) targeting DLL3 and CD3—marks a pivotal advancement, demonstrating improvement in survival in refractory disease. This review examines three key advances reshaping SCLC management: (1) mechanistic links between DLL3-driven tumorigenesis and PD-L1-mediated immunosuppression, (2) clinical progress in antibody-drug conjugates (ADCs) with next-generation payloads (e.g., FZ-AD005), multispecific BiTEs (e.g., HPN328), and engineered CAR-T/NK cells with enhanced metabolic resilience, and (3) precision strategies combining liquid biopsy for dynamic DLL3 profiling with immuno-PET imaging using [89Zr]Zr-DFO-SC16. Emerging synergies, such as combining DLL3-targeted BiTEs with ICIs to amplify T-cell infiltration or reprogramming CAR-T mitochondrial metabolism, further underscore the potential of multimodal approaches. Together, these developments signal a transformative era in SCLC treatment, where molecular diagnostics and engineered immunotherapies converge to address unmet clinical needs.